DESIGN ON STEP-TYPE ADVANCED SUPPORTING SYSTEM AND RESEARCH ON THE SUPPORTING CHARACTERISTICS - XIE Miao; LIU ZhiXiang; MAO Jun; LU JinNan; CHI Cheng (Jixie qiangdu)
In order to improve the driving efficiency,and support technology,design a kind of stepping-type advanced supporting equipment which can be used for supporting on fully mechanized tunnelling. Analysis the mechanical characteristics of the roof of roadway and the working principle of the advanced supporting equipment,and establish the mechanics model of the advanced supporting equipment with roof. Establish the deflection equation of roof by the theory of structural mechanics and materials mechanics,and solve the deformation law of the roof with the help of computer aided software. Simulate the deformation of roof and supporting equipment using ANSYS software. Build advanced supporting prototype,and carry out simulation experiments about supporting characteristics combined with the simulation of roof. The simulation and experimental results show that,the roof has been supported effectively with the help of advanced supporting equipment,and the equipment has high value in engineering application.